Quasilinear dirichlet problems in RN with critical growth - Silva, Elves A. B. E; Soares, Sérgio H.M. (Elsevier, 2001)
In this study, a given quasilinear problem is solved using variational methods. In particular, the existence of nontrivial solutions for GP is examined using minimax methods. The main theorem on the existence of a nontrivial solution for GP is detailed.
Keywords: Boundary conditions; Laplace transforms; Parameter estimation; Perturbation techniques; Set theory; Theorem proving; Ambrosetti-Rabinowitz condition; Concentration compactness principle; Critical Sobolev exponent; Dirichlet problem; Mountain pass theorem; Quasilinear problem; Variational techniques